2015
DOI: 10.53879/id.52.11.10325
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Study of Cyclodextrin Inclusion Complex on Enhancement of Solubility of Aceclofenac

Abstract: The main objective of the present study was to enhance the solubility and dissolution rate of poorly water soluble aceclofenac using its solid dispersion with β-cyclodextrin. FTIR and DSC study was carried out to find out any incompatibility. The phase solubility of drug was carried out in 1, 2, 5, and 10% of β-cyclodextrin in distilled water. Kneading method and solvent evaporation method was use to prepared solid dispersion of aceclofenac and β-cyclodextrin. Different evaluation tests like solubility study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thermal studies of β-CD with aceclofenac inclusion complex supports the present study that β-CD exhibited a melting peak at 109 °C. 21 Although both the peaks were found in the same range, slight reduction was noted in the R-β-CD. The temperature difference indicated that β-CD might undergo slight modification after cholesterol removal and during recycling process.…”
Section: Resultsmentioning
confidence: 85%
“…Thermal studies of β-CD with aceclofenac inclusion complex supports the present study that β-CD exhibited a melting peak at 109 °C. 21 Although both the peaks were found in the same range, slight reduction was noted in the R-β-CD. The temperature difference indicated that β-CD might undergo slight modification after cholesterol removal and during recycling process.…”
Section: Resultsmentioning
confidence: 85%
“…The DSC curve for -CD and -CDX3 were demonstrated in Figure 4 (c). Figure 4 (c) states that the endothermic peak of -CD observed at around 93 o C its melting point [30] that means -CD is heat absorbed, but in case of -CDX3 the multiple exothermic peaks observed at 55, 236, 260 & 399 o C. The major exothermic peak of -CDX3 were occurred at around 236 o C its melting point that means -CDX3 is heat released. From above observation it is clear that the -CDX3 is quite stable than that of -CD.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 98%
“…The relationship between the temperature change and mass loss is expressed using DSC (Differential Scanning Calorimetry) and the DSC plot of the surface-modified Bi 2O3 NP system is shown in Figure 5 [41][42][43]. On increasing the temperature from room temperature, in the DSC plot, an endothermic peak was observed where the onset temperature, the peak temperature, and the end set temperature are at 54.22 °C, 78.19 °C, and 104.23 °C, respectively.…”
Section: Thermal Studiesmentioning
confidence: 99%